REDESAIN KEMASAN DALAM MENINGKATKAN BRAND AWARNESS PRODUK UNGGULAN UKM CILODONG BERKARYA - Yani Hendrayani; Hermina Manihuruk (Jurnal Bakti Masyarakat Indonesia, 2020)
Product packaging design is one important factor that can strengthen the branding of MSME businesses in increasingly fierce business competition. Attractive and quality packaging design is the differentiator from competitors. For this reason, the idea of product packaging for UKM Cilodong Berkarya needs to get attention for the redesign of each product to be marketed. For this reason, community engagement is carried out to find out the extent of the understanding of the UKM Cilodong Berkarya entrepreneurs regarding the importance of Product Packaging Design and continued with the design of the right packaging design for its products to enhance brandawarness and superior products. The purpose of this activity is to build brand awareness from the redesign of product packaging products that were launched by UKM Cilodong Berkarya Berkarya Kota Depok. The method of activity through mentoring and training in product packaging redesigning is more attractive to consumers by choosing one of the superior products. The target of the output is to make an alternative product packaging for one of the superior products, namely Alevera Tea, which was launched by UKM Cilodong Berkarya in the City of Depok. The results of community engagement regarding packaging redesign are related to the shape, structure, material, color, image, typography, and design elements with product information so that the product can be marketed. Redesign of packaging in the form of designing old packaging into new packaging to make it more attractive, so that it has the maximum function applicable to wrapping, protecting, sending, issuing, storing, identifying, and differentiating a product on the marketABSTRAK:Desain kemasan produk merupakan salah satu faktor penting yang dapat menguatkan branding usaha UMKM dalam persaingan bisnis yang semakin ketat. Desain kemasan yang menarik dan berkualitas menjadi pembeda dari kompetitor. Untuk itu ide kemasan  produk UKM Cilodong Berkarya Berkarya perlu mendapatkan perhatian untuk redesain  pada setiap produk yang akan dipasarkan. Untuk itu dilakukan pengabdian masyarakat  untuk mengetahui sejauh mana pemahaman para pengusaha UKM Cilodong Berkarya terkait tentang pentingnya Desain Kemasan Produk dan dilanjutkan dengan perancangan desain kemasan  yang tepat bagi produk produknya untuk meningkatkan brandawarness dan produk unggulan. Adapun tujuan kegiatan ini adalah  membangun brand awareness (kesadaran akan merek) dari redesaign kemasan produk produk yang diluncurkan UKM Cilodong Berkarya Berkarya Kota Depok. Metode kegiatan melalui pendampingan dan pelatihan  redesigning kemasan produk yang lebih menarik konsumen dengan memilih salah satu produk unggulan. Target luaran adalah dibuatkan alternatif kemasan kemasan produk untuk salah satu  produk unggulan yaitu teh aloevera yang diluncurkan UKM Kota Cilodong Berkarya Kota Depok. Hasil dari pengabdian masyarakat tentang redesain kemasan berkaitan pada bentuk, struktur, material, warna, citra, tipografi, dan elemen elemen desain dengan informasi produk agar produk dapat dipasarkan. Redesain kemasan berupa mendesain kemasan lama menjadi kemasan baru agar lebih menarik, sehingga memiliki fungsi yang maksimal berlaku untuk membungkus, melindungi, mengirim, mengeluarkan, menyimpan, mengidentifikasi, dan membedakan sebuah produk di pasar